“Oh, a polícia parou!!! a polícia parou!!!”: o movimento reivindicatório realizado pelos militares estaduais do Maranhão no ano de 2011 - JESUS, Paulo Henrique Matos de (2020)
The main objective of this dissertation is to investigate and understand the organization and dynamics of the claimet movement carried out by the state military of Maranhão in 2011, examining the possibility of connection with the institutional, legal and political dimensions historically established in the national and state context, especially as the experiences of these subjects were manifested in this dynamic and in the construction of an individual and collective memory about them. In turn, the complementary and specific objectives will be to describe and analyze the ways in which the idea of Security was applied in Brazil, highlighting key moments to understand under which foundations the elaboration and application of its concept occurred in the country, especially between the years 1964 and 2011. Analyze the philosophy of Community Policing and look for connections between the experiences of the cities of New York (USA); Bogotá and Medellín (Colombia), São Paulo, Rio de Janeiro and São Luís (Brazil). Describe and analyze the narratives of the memories surrounding the 2011 claimet movement, based on the oral reports obtained in structured and unstructured interviews conducted with the state military members participating or not in the movement and its dissemination in the media (print and digital) local and national as an instrument through which it will seek to understand and explain the intricacies of this complex event.